Emotional intelligence and self-efficacy career decision making among high school students - Muhamad Syamiezy Sidek; Abu Yazid Abu Bakar (Education and Social Sciences Review, 2020)
Lack of self-confidence in decision making is one of the dominant problems that often engage students in making career choices. This study aimed to answer three research questions, namely, 1) is there a difference in emotional intelligence based on gender, 2) is there a difference in self-efficacy in career decision making among form four based on gender factors, 3) is there a relationship between emotional intelligence and self-efficacy making career decisions among form four students. The study sample was 80 respondents in a secondary school. This study is a survey study and uses the Emotional Intelligence test as well as the Career Decision Self-Efficacy test (CDSE-SF). The data were analyzed using SPSS version 24. The results showed that there was no difference between emotional intelligence and self-efficacy based on gender. Besides, the study also found no relationship between emotional intelligence and self-efficacy in career decision making. This study supports counselors and various working groups with adolescents to assist students in their career path from school to school.